"THE PROTECTIVE ROLE OF L-CYSTEINE AGAINST FOLLICULAR ATRESIA INDUCED BY LEAD IN MOUSE OVARY" - M. Azarnia; A. Shakour; P. Rostami A. Sanaie-Mehr (Acta Medica Iranica, 2004)
Lead is an ubiquitous environmental toxin that induces a broad range of physiological biochemical, and behavioral dysfunctions. In this study, we examined the pathologic effects of lead acetate in NMRI mouse ovarian tissue and the protective role of antioxidant L-cysteine, against the induced damage. We used lead acetate at a dose of 10 mg/kg, and L-cysteine at a dose of 200 mg/kg. Both drugs were administered intraperitoneally according to 2 protocols: intraperitoneal injection of lead acetate 10 mg/kg/day for 15 days or 10 mg/kg/week for 15 weeks. Ovaries were examined histologically and changes in the number of graafian, growing, atretic, and primordial follicles, thickness of granolusa of theca layers, relative ovary weight (ROW) and animal weights, were determined. Significantly increased numbers of atretic follicles and thickness of the theca layer, and a decrease in other parameters were observed after treatment with lead acetate (P< 0.05). No changes were observed after treatment with a combination of L-cysteine. Also, more oocytes had resumed meiosis in the follicles exposed to lead acetate. The results suggest that lead acetate at a dose of 10 mg/kg has a toxic effect on ovarian tissue, and antioxidants such as L-cysteine have a protective role against the induced damage.